2015
DOI: 10.1242/jeb.127407
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and thermal sensitivity of ballistic and non-ballistic feeding in salamanders

Abstract: Low temperature reduces the performance of muscle-powered movements, but in movements powered by elastic recoil mechanisms, this effect can be mitigated and performance can be increased. To better understand the morphological basis of high performance and thermal robustness of elastically powered movements, we compared feeding dynamics at a range of temperatures (5-25°C) in two species of terrestrial plethodontid salamanders, Plethodon metcalfi and Ensatina eschscholtzii, which differ in tongue muscle architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(63 citation statements)
references
References 53 publications
6
56
1
Order By: Relevance
“…In vivo studies have found that performance of feeding behaviors that utilize elastic-recoil mechanisms is maintained despite changing temperature and the effects on muscle contractile physiology (Anderson and Deban, 2010;Anderson et al, 2014;Deban and Lappin, 2011;Deban and Richardson, 2011;Deban and Scales, 2016;Scales et al, 2016). Because these salamanders, toads and chameleons are maintaining performance at lower temperatures, their muscles must be shortening to do work with relatively low forces, provided that P 0 is affected by temperature as we have shown in the present study.…”
Section: Impacts On Elastically and Muscle-powered Movementssupporting
confidence: 57%
See 2 more Smart Citations
“…In vivo studies have found that performance of feeding behaviors that utilize elastic-recoil mechanisms is maintained despite changing temperature and the effects on muscle contractile physiology (Anderson and Deban, 2010;Anderson et al, 2014;Deban and Lappin, 2011;Deban and Richardson, 2011;Deban and Scales, 2016;Scales et al, 2016). Because these salamanders, toads and chameleons are maintaining performance at lower temperatures, their muscles must be shortening to do work with relatively low forces, provided that P 0 is affected by temperature as we have shown in the present study.…”
Section: Impacts On Elastically and Muscle-powered Movementssupporting
confidence: 57%
“…Many ectotherms bypass the limitations of muscle contraction and maintain performance at lower temperatures by using elastic-recoil mechanisms in their feeding movements (chameleons: Anderson and Deban, 2010;toads: Deban and Lappin, 2011;salamanders: Anderson et al, 2014;Deban and Richardson, 2011;Deban and Scales, 2016;Scales et al, 2016). These animals are able to use their muscles to stretch elastic connective tissue, storing energy that is later released rapidly when this tissue recoils (de Groot and van Leeuwen, 2004;Deban et al, 2007;Lappin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in temperature present a significant challenge to organisms, especially ectotherms; low temperature can result in substantial decreases in ecologically relevant performance such as predator escape and feeding (Huey and Bennett, 1987;John-Alder et al, 1989;Lutz and Rome, 1996;Wintzer and Motta, 2004;Devries and Wainwright, 2006;Herrel et al, 2007;Deban and Scales, 2016;Scales et al, 2016). Reductions in performance such as running and swimming velocities and jumping distances primarily result from lower muscle contractile rates that can decline by half over a 10°C drop in temperature (Bennett, 1984(Bennett, , 1985Hirano and Rome, 1984;Bauwens et al, 1995;Lutz and Rome, 1996;Peplowski and Marsh, 1997;Navas et al, 1999;Donley et al, 2007;Herrel et al, 2007;James, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, in movements powered by elastic recoil, these temperature effects are largely mitigated by temporally decoupling muscle contraction from the movement itself. For example, ballistic tongue projection in chameleons, toads and salamanders is thermally robust (Q 10 <2) and even temperature independent in some cases (Deban and Richardson, 2011;Deban and Lappin, 2011;Anderson and Deban, 2012;Deban and Scales, 2016). In these systems, the reduced temperature sensitivity does not appear to result from compensatory muscle activity at low temperatures or atypical muscle contractile physiology (Deban and Lappin, 2011;Anderson and Deban, 2012;Anderson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%